Perceptions and associated factors with the oral health and dental care in perinatal period in women and their babies - Concha Sánchez, Sonia Constanza (2020)
Objective. To understand the factors associated with oral health and dental care in the perinatal period in women and their babies. Methods. Supported in the critical theory and collective health, a qualitative and quantitative study was carried out. In the qualitative one, supported by symbolic interactionism, interviews were conducted on 18 postpartum women. The quantitative one was an observational cross-sectional study on 40 women. The explanatory and output variables for qualitative study were analyzed using Chi2 test and the quantitative using Student's T-test. Results. In the qualitative approach, women give aesthetic importance to oral health, without relating it to their general health and that of the baby; dental care is difficult in postpartum period and they do not consider it important for their babies. In quantitative terms, 15% of women did not attend the dental care during pregnancy, associated with the baby's born days number. 82.5% of the women did not attend it during the postpartum period, being associated it with the health affiliation regime. 72.5% of moms did not perceive the need of attention for their babies, being associated it with a money lack for transportation. Conclusions. The results indicate the need to promote better constructions on oral health and dental care for the evaluated mothers. Sociodemographic variables, social position, and women’s oral health were associated with non-attendance of the dental attention during pregnancy, the postpartum period and the mother perception of the baby's need for treatment.